Polar bears - Mason, Conrad; Howarth, Daniel (Tulsa, Okla. : EDC, 2009)
Illustrations and simple text introduce young readers to the world of polar bears, how they swim, hunt, play, and care for their cubs.
Includes index.
2.2
K-3
Keywords: Bears; Polar bears; Bears; Polar bears; Readers (Elementary).